Stable biological production in the Eastern Equatorial Pacific Across the Plio-Pleistocene transition (∼3.35-2.0 Ma) - Jakob, Kim; Ho, S. Ling; Meckler, A. Nele; Pross, Jörg; Fiebig, Jens; Keppler, Frank; Friedrich, Oliver (Paleoceanography and paleoclimatology, 2021)
Upwelling within the Eastern Equatorial Pacific (EEP) Ocean is a key factor for the Earth's climate because it supports >10% of the present-day biological production. The dynamics of upwelling in the EEP across the Plio-Pleistocene transition—an interval particularly relevant for understanding near-future warming due to Anthropocene-like atmospheric carbon-dioxide levels—have been intensively studied for the region east of the East Pacific Rise. In contrast, changes of the equatorial upwelling regime in the open Pacific Ocean west of this oceanographic barrier have received markedly less attention. We therefore provide new proxy records from Ocean Drilling Program Site 849 located within the EEP open-ocean upwelling regime. Our target interval (∼3.35-2.0 Ma) covers the Plio-Pleistocene transition characterized by the intensification of Northern Hemisphere Glaciation (iNHG). We use benthic δ18O values to generate a new, high-resolution age model for Site 849, and sand-accumulation rates together with benthic δ13C values to evaluate net export production. Although showing temporary substantial glacial-interglacial variations, our records indicate stability in net export production on secular timescales across the iNHG. We suggest the following processes to have controlled the long-term evolution of primary productivity at Site 849. First, nutrient export from the high latitudes to the EEP; second, a successive shoaling of the Pacific nutricline during the studied interval; and third, a simultaneous reduction in dust-borne iron input.